2017
DOI: 10.1084/jem.20171022
|View full text |Cite
|
Sign up to set email alerts
|

Stochasticity enables BCR-independent germinal center initiation and antibody affinity maturation

Abstract: Whether Ig engagement by antigen is required to initiate somatic evolution and affinity maturation is not well defined. Silver and colleagues show that germinal center flexibility permits nonspecific B cells to achieve de novo antigen recognition and antibody affinity maturation.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

6
23
0

Year Published

2018
2018
2023
2023

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 33 publications
(29 citation statements)
references
References 36 publications
(47 reference statements)
6
23
0
Order By: Relevance
“…In contrast, acquisition of T cell help is sufficient to induce GC B cell expansion and PB formation, even in the absence of BCR engagement with Ag. These findings are consistent with a recent study that showed that, in the presence of abundant T cell help, non-Ag-specific B cells could participate in GCs and persist long enough to acquire specificity to Ag (Silver et al, 2018). Although loading GC B cells with T cell Ag peptides was sufficient to promote their selection and PB differentiation in a dose-dependent fashion (Figures 1L–1N; Gitlin et al, 2014), we found that Ag-dependent BCR engagement potentiated GC B cell expansion and PB differentiation when the amount of T cell Ag peptide loaded was subsaturating.…”
Section: Resultssupporting
confidence: 93%
“…In contrast, acquisition of T cell help is sufficient to induce GC B cell expansion and PB formation, even in the absence of BCR engagement with Ag. These findings are consistent with a recent study that showed that, in the presence of abundant T cell help, non-Ag-specific B cells could participate in GCs and persist long enough to acquire specificity to Ag (Silver et al, 2018). Although loading GC B cells with T cell Ag peptides was sufficient to promote their selection and PB differentiation in a dose-dependent fashion (Figures 1L–1N; Gitlin et al, 2014), we found that Ag-dependent BCR engagement potentiated GC B cell expansion and PB differentiation when the amount of T cell Ag peptide loaded was subsaturating.…”
Section: Resultssupporting
confidence: 93%
“…low DND). This is consistent with data showing low affinity survivors in GCs (Kuraoka et al, 2016) or the persistence of unrelated BCs in the GC reaction (Silver et al, 2018). More generally speaking, GCs in the DisseD-theory are more permissive than in the other theories.…”
Section: Discussionsupporting
confidence: 90%
“…One might consider this experimental system artificial and non-physiological. However, a realistic theory of BC selection has to properly describe GCs permissive of low affinity BCs (Kuraoka et al, 2016;Silver et al, 2018) still allowing for efficient affinity maturation, diversity of GC clonal dominance (Tas et al, 2016) still allowing for clonal bursts, Tfh signal-dependent DND upon selection without losing the relevance of BCR signaling for selection, and also reflect extreme stimulation settings like antigen-uptake via the DEC205-receptor . A consistent theory, explaining these seemingly conflicting GC properties does not exist (Oprea & Perelson, 1997;Zhang & Shakhnovich, 2010;Meyer-Hermann et al, 2012;Wang et al, 2016;de Boer & Perelson, 2017;Meyer-Hermann, 2019).…”
Section: Introductionmentioning
confidence: 99%
“…The TD-3 response is less likely to occur between resting B and T cells, but occurs between activated B and T cells upon infection or other pathogenic stimuli. The non-cognate or bystander interaction between T and B cells is important for the overall Ab responses as previously reported ( 57 66 67 68 ). Another example of non-cognate B cell help via MHC class II is when CD4 + T cell recognizes idiotypic peptides from immunoglobulin heavy chain variable domain present within the MHC class II molecule ( 64 ).…”
Section: Suggestion Of a New Sub-classification Of Td Ab Responsessupporting
confidence: 61%